ZASADA RÓWNEGO TRAKTOWANIA AKCJONARIUSZY W KODEKSIE SPÓŁEK HANDLOWYCH - ZAGADNIENIA PODSTAWOWE - Sójka, Tomasz (Wydział Prawa i Administracji UAM, 2000)
The principle of equal treatment of shareholders is one of the instruments of protection of minority shareholders within a company. In the project discussed in the article we can see this principle in a descriptive way - as a well determined pattern of shaping organizational structure of a joint stock company. Such a pattern is composed with a series of different norms preferring just such a mode of regulating relations between a company and its shareholders. Such an approach offers some axiological premises which should be of distinct importance within the process of functional interpretation o f particular norms relating to the law companies. The principle discussed can also be comprehended in a directional sense; firstly - as a particular postulate of legislation politics and - secondly - as a binding norm of the system of law. In normative sense it results from the principle an obligation for a share stock company to treat equally (in the same circumstances) all its shareholders - with the only reservation made for the exceptions admitted by the law and statutes and motivated with the interest of the company. The introduction o f the article 20 into the Project of the Law on Commercial Companies shall not change essentially respective legal situation in comparison with regulations of the Commercial Code dated 1934.
PRINCIPLE OF EQUAL TREATMENT OF SHAREHOLDERS IN THE CODE OF COMMERCIAL COMPANIES. FUNDAMENTAL ISSUES